(untitled) (Research, Society and Development, 2022)
Objective: To report, based on the scientific literature, how nursing care for women’s health is carried out in primary care, seeking to describe its benefits and discussing its functioning. Methodology: This is an integrative literature review of an exploratory and quantitative nature, carried out in the following databases: Medical Literature Analysis and Retrieval System Online (MEDLINE), Latin American and Caribbean Literature on Health Sciences (LILACS), Scientific Electronic Library Online (SCIELO) and Nursing Database (BDENF), articles written in Portuguese, published between 2017 and 2021 were used. Results: A total of 537 articles were found, after methodological rigor through the inclusion criteria and exclusion, 11 articles were selected, 0 in MEDLINE, 5 in LILACS, 0 in SCIELO and 6 in BDENF. The verification of the information was done in a descriptive way and predisposed the stage of data extraction: author, title, type of study, objective and year of publication. Conclusion: The study showed that in primary care, nursing shows an indispensable influence, that according to the regulations and policies assigned to nurses about their care, ethical and management character, there are common sense issues that professionals must compose to guarantee care continuous.